Traço falciforme é um fator preditor para doenças periodontais? - CARVALHO , Halinna Larissa Cruz Correia de (2014)
Background: Sickle Cell Trait (SCT) is characterized by heterozygous inheritance of a gene for normal hemoglobin (HbA) and one abnormal gene for beta globin mutation in hemoglobin, yielding a modified hemoglobin (HbS). It is traditionally described as a benign condition, however, in situations of low oxygen tension, individuals with higher concentrations of HbS may suffer vasoocclusive events, causing ischemia, infarction, necrosis and possible inflammation and susceptibility to bacterial infections. Periodontal diseases (PDs) are chronic conditions triggered in response to bacterial colonization and its clinical manifestations are strongly influenced by the host immune response, also modulated by genetic risk factors. Individuals with SCT seem to be more susceptible to bacterial infections and may therefore be more prone to PDs. The aim of this study was to investigate the association between TF and PDs through evaluation of clinical and radiographic features. Material and Methods: This was a retrospective cohort study. The subjects were selected from Supervision of Hematology and Hemotherapy of Maranhão (HEMOMAR) in São Luís, Brazil and were divided into 3 groups: exposed group 1 (with Sickle Cell Anemia (SCA); exposed group 2 (with SCT) and group unexposed (no SCA and SCT), with 123 patients per group (n = 369). Plaque index (PI), gingival index (GI), calculus index (CI), probing depth (PD), clinical attachment level (CAL), gingival recession (GR), tooth mobility and furcation involvement were clinically evaluated. For radiographic evaluation, the percentage of alveolar bone loss was measured employing the Schei ruler. Binomial and Poisson regressions were used to estimate the associations of interest (p<0.05). Results: In adjusted analysis, PI was lower in individuals with SCT (p = 0.044), whereas CI and bone loss were higher (p=0.003 and p=0.10, respectively) compared to unexposed group. SCT was associated with gingivitis (p=0.041) and periodontitis (p=0.002) even after adjustment for covariates. Conclusion: SCT can act with a predictive factor for PD´s establishment.